The Ethics of Ambiguity - Ronald E. Domen MD (Elsevier, 2016)
Understanding and embracing uncertainty are critical for effective teacher-learner relationships as well as for shared decision-making in the physician-patient relationship. However, ambiguity has not been given serious consideration in either the undergraduate or graduate medical curricula or in the role it plays in patient-centered care. In this article, the author examines the ethics of ambiguity and argues for a pedagogy that includes education in the importance of, and tolerance of, ambiguity that is inherent in medical education and practice. Common threads running through the ethics of ambiguity are the virtue of respect, and the development of a culture of respect is required for the successful understanding and implementation of a pedagogy of ambiguity.